2021
DOI: 10.1186/s12935-021-01866-3
|View full text |Cite
|
Sign up to set email alerts
|

FZD2 promotes TGF-β-induced epithelial-to-mesenchymal transition in breast cancer via activating notch signaling pathway

Abstract: Background Breast cancer (BC) is one of the commonest female cancers, which is characterized with high incidence. Although treatments have been improved, the prognosis of BC patients in advanced stages remains unsatisfactory. Thus, exploration of the molecular mechanisms underneath BC progression is necessary to find novel therapeutic methods. Frizzled class receptor 2 (FZD2) belongs to Frizzled family, which has been proven to promote cell growth and invasion in various human cancers. The purp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…Furthermore, our results indicated that Notch1 protein was widely distributed in the cytoplasm of Huh7 cells, which was consistent with previous findings that Notch1 protein was mainly allocated in the cytoplasm rather than the nucleus of HCC cells [ 48 , 49 ]. Moreover, we found that Jagged1, a ligand of Notch signaling, was widely presented in the cytoplasm of Huh7 cells, but it could be inhibited by PAB and DAPT (a Notch signaling inhibitor), resulting in a significant reduction in the expression of Notch1 protein.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, our results indicated that Notch1 protein was widely distributed in the cytoplasm of Huh7 cells, which was consistent with previous findings that Notch1 protein was mainly allocated in the cytoplasm rather than the nucleus of HCC cells [ 48 , 49 ]. Moreover, we found that Jagged1, a ligand of Notch signaling, was widely presented in the cytoplasm of Huh7 cells, but it could be inhibited by PAB and DAPT (a Notch signaling inhibitor), resulting in a significant reduction in the expression of Notch1 protein.…”
Section: Discussionsupporting
confidence: 92%
“…If we look at the changes of single genes, it is striking that Frizzled class receptor 2 ( FDZ2 ) is the only gene that is significantly upregulated in adenomyosis compared to DIE. FZD2 is discussed as an important trigger of TGF-ß induced epithelial–mesenchymal transition (EMT) [ 38 ] and cell migration [ 39 ]. Accordingly, the induction of EMT and ultimate fibrosis by TGF-β1 appears to play a critical role in the pathogenesis of adenomyosis [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“… 112 Interestingly, recent research indicates that Notch signaling participates in the EMT induction mediated by TGF‐β, and this process is mediated via the TGF‐β‐triggered phosphorylated SMAD3. 113 , 114 …”
Section: Signaling Pathways Regulating Empmentioning
confidence: 99%